Does Knee Hyperextension Affect Dynamic In Vivo Kinematics and Clinical Outcomes after Anterior Cruciate Ligament Reconstruction?. Issue 7 (21st July 2017) - Nagai, Kanto; Gale, Tom; Tashiro, Yasutaka; Herbst, Elmar; Irrgang, James J.; Anderst, William; Fu, Freddie H.; Tashman, Scott
Objectives: There is no consensus on whether knee hyperextension affects postoperative outcome after anterior cruciate ligament reconstruction (ACL-R). A limitation of previous studies is that they evaluated only static joint laxity. The purpose of this study was to evaluate the effect of dynamic hyperextension on postoperative dynamic in vivo kinematics and clinical outcomes. It was hypothesized that patients with a high degree of knee hyperextension in the contralateral normal knee would have larger ranges of anterior translation and internal-external rotation of the ACL reconstructed knee during dynamic activities, and lower patient-reported outcome (PRO) subjective scores compared to the patients who have less contralateral knee hyperextension. Methods: Forty-one patients (22±8 y.o., 27 male / 14 female) underwent unilateral ACL-R. According to the maximum extension angle of the contralateral normal knee during gait using dynamic stereo X-ray (DSX) images, subjects were divided into 2 groups at the median value (4.7°): Hyperextension group (n = 21, knee extension: 7.8±2.2°), and Normal extension group (n = 20, knee extension: 2.4±2.0°). Six and twenty-four months after ACL-R, subjects performed level gait and downhill running on a treadmill while DSX images were acquired at 100Hz (gait) or 150Hz (running). Tibiofemoral motion was determined from DSX images using a previously validated model-based tracking process, and tibiofemoral translations/rotations from initial contact to initial loading (gait cycle: 0-10%) were calculated. The side-to-side differences (SSD) of range of tibiofemoral motions at 6 and 24 months after surgery were calculated. KT-1000 measurements and PRO (IKDC Subjective Knee Form and KOOS scores) at 24 months after surgery were also evaluated. Results of kinematics were analyzed using 2-way repeated-measures ANOVA, and the SSD of kinematics, KT-1000 measurements and PROs were analyzed using student t-test ( P < 0.05). Results: The ACL reconstructed knee was significantly more extended in Hyperextension group than in Normal extension group at 6 months (3.9±4.7° vs -0.5±5.3°, P = 0.007) and 24 months (4.8±3.2° vs 0.5±4.6°, P = 0.001) after surgery. Regarding the kinematics of affected knees, there were no significant differences in anterior translation or internal rotation between the 2 groups at 6 months and 24 months after surgery, although there were trends of increased anterior translation and internal rotation over time in both groups (Figure 1). Even in SSD, there was no significant difference between 2 groups. There were also no significant differences in terms of KT-1000 measurements and PRO. Conclusion: This is the first study to assess the effect of dynamic knee hyperextension on in vivo kinematics after ACL reconstruction. The main findings of this study were that there were no significant differences of dynamic in vivo kinematics and clinical outcomes between Hyperextension and Normal extension groups, contrary to the hypothesis. Although knee hyperextension is believed to be a risk factor for poor outcome, the results of this study do not show significant influence of knee hyperextension on the functional kinematics and clinical outcomes after ACL-R. Figure 1. Mean knee kinematics during downhill running in affected knees. There was no significant difference in anterior tibial translation (A) or internal rotation (B) between two groups at both six and twenty-four months after surgery (n.s.: not significant).